LO81: Optimizing the use of CT scanning for pulmonary embolism in the emergency department. (15th May 2017) - Sharif, S.; Kearon, C.; Li, M.; Eventov, M.; Sneath, P.E.; Leung, R.; Jiang, R.; de Wit, K.
Abstract : Introduction: Diagnosing pulmonary embolism (PE) can be challenging because the signs and symptoms are often non-specific. Studies have shown that evidence-based diagnostic algorithms are not always adhered to in the Emergency Department (ED), which leads to unnecessary CT scanning. In 2013, the American College of Chest Physicians identified CT pulmonary angiography as one of the top five avoidable tests. One solution is to use a clinical prediction rule combined with the D-dimer, which safely reduces the use of CT scanning. The objective of this study was to compare the proportion of patients tested for PE in two emergency departments, who 1) had a CT-PE and 2) whose diagnosis of PE was missed. We compared these rates to those if the Wells rule and D-dimer had been applied as standard.Methods: This was a retrospective chart review of ED patients investigated for PE at two hospitals from April 2013 to March 2015 (24 months). Inclusion criteria were the ED physician ordered CT-PE, Ventilation-Perfusion (VQ) scan or D-dimer for investigation of PE. Patients under the age of 18 were excluded. PE was defined as CT/VQ diagnosis of acute PE or acute PE/DVT in 30-day follow-up. Trained researchers extracted anonymized data. The rate of CT/VQ imaging and the false-negative rates were calculated. The false-negative rate was calculated as the number of patients diagnosed with PE within 30 days as a proportion of those patients who did not have a CT/VQ scan at initial presentation.Results: There were 1, 189 patients included in this study. 55/1, 189 patients (4.6%; 95%CI 3.6-6.0%) were ultimately diagnosed with PE within 30 days. 397/1, 189 patients (33.4%; 95%CI 30.8-36.1%) had CT/VQ scans for PE. 3 out of 792 who were not scanned had a missed PE resulting in a false-negative rate of 0.4% (95% CI 0.1-1.1%). 80 patients had an elevated D-dimer or high Wells score but were not imaged. Furthermore, 75 patients who did not have an elevated D-dimer nor a high Wells score were imaged. Had Wells rule/D-dimer been adhered to, 402/1, 189 patients (33.8%; 95%CI 31.9-36.6%) would have undergone imaging and the false negative rate would be 0/727, 0% (95%CI 0.0-0.5%).Conclusion: If the Wells rule and D-dimer was used in all patients tested for PE, a similar proportion would have a CT scan but fewer PEs would be missed.